Martin Buber and Social Justice - Margulies, Hune (Religions, 2023)
Martin Buber’s seminal work is his “I and Thou”. In I and Thou, Buber establishes a philosophical foundation for the creation of a dialogical society. Buber’s concept of I–Thou dialogue provides a framework for understanding the inherent connection between interpersonal encounters and social justice. As Buber elucidates, genuine dialogue is not confined to the encounter between two persons, but it manifests in the manner of a society organized on premises of social justice, freedom and compassion. In this regard, it is important to note that if we trace Buber’s personal and philosophical biography we will not find many instances of him engaging in what could be called social justice activism. Buber did found and join civic organizations that dealt with issues of peace and justice, and lent his support to many such political endeavors (see the organizations called Brith Shalom (Covenant of Peace) founded in 1925 in mandatory Palestine, and Ihud (Unity) founded in 1942, six years before Israel’s statehood). Nonetheless, a number of world prominent social justice advocates and activists found inspiration and guidance in Buber’s philosophy, and it is perhaps hereby, where Buber’s impact on social justice is most distinctly pronounced. What Buber aimed to achieve in his writings and political endeavors was to present a philosophy of relationships on which to found a society established on practices of social justice.